Expression of Dopamine-Related Genes in Four Human Brain Regions - Stanfill, Ansley Grimes (Brain Sci, 2020)
A better understanding of dopaminergic gene expression will inform future treatment options for many different neurologic and psychiatric conditions. Here, we utilized the National Institutes of Health’s Genotype-Tissue Expression project (GTEx) dataset to investigate genotype by expression associations in seven dopamine pathway genes (ANKK1, DBH, DRD1, DRD2, DRD3, DRD5, and SLC6A3) in and across four human brain tissues (prefrontal cortex, nucleus accumbens, substantia nigra, and hippocampus). We found that age alters expression of DRD1 in the nucleus accumbens and prefrontal cortex, DRD3 in the nucleus accumbens, and DRD5 in the hippocampus and prefrontal cortex. Sex was associated with expression of DRD5 in substantia nigra and hippocampus, and SLC6A3 in substantia nigra. We found that three linkage disequilibrium blocks of SNPs, all located in DRD2, were associated with alterations in expression across all four tissues. These demographic characteristic associations and these variants should be further investigated for use in screening, diagnosis, and future treatment of neurological and psychiatric conditions.